The Extraction of Anthocyanin From Clitoria Ternatea (Blue Pea Flower) by Using Spray Dryer - Syazwani, Sapiee (2013)
Nowadays, interest in anthocyanin pigments shows an increasing tendency due to their possible health benefits as antioxidants, anti-inflammatory, anti-viral, protection from cardiovascular damage, diabetes preventation and vision improvement. Clitoria ternatea, a local flower which also an indigenous climber herbs, has been found to produce pigments mostly anthocyanin. In this research, anthocyanin from Clitoria ternatea, also known as blue pea flower was extracted by using water. The anthocyanin extract were encapsulated by using spray dry method, which three parameters are being studied, that are inlet air temperature, maltodextrin addition, and also feed flow rate. The technique of using spray dryer is preferable as transformation of juices into dry powders is quite hard due to the high sugar and acid contents. The experimental research was done by using Laboratory Scale Spray Dryer SD06AG, with the range of 160°C to 190°C of temperature, maltodextrin addition of 0% to 40% and feed flow rate of 5 ml/min to 20 ml/min. Further analysis on the quality of the powder obtained from spray drying process were verified by measuring total phenol content, anthocyanin content and antioxidant activity by using UV-Vis U 1800 Spectrophotometer at certain wavelengths. Maltodextrin DE10 had been used as carrier in the spray dryer to prevent wall-deposition formation during the process. As result indicates that at 170°C of inlet temperature, with 30 % maltodextrin addition and 10 ml/min of feed flow rate is the best condition to encapsulate CTAE by using spray dry.